2005
DOI: 10.1111/j.1468-2451.2009.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Governance strategies to remedy the natural resource curse

Abstract: Rising commodity prices in recent years have deepened awareness of the paradox of the resource curse – resource‐rich countries consistently facing high levels of poverty, corruption and instability. There is relatively less recognition of the autocratic roots underlying much of this curse, however. Resource‐rich autocracies, on average, are subject to lower levels of well‐being, higher volatility, a greater propensity for conflict and humanitarian crisis, and more corruption than resource‐rich countries on a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Volatility in oil and mineral prices may thus have large impacts on the overall economy and on government budgets, causing greater uncertainty and lower growth (Havro and Santiso, 2008). A standard measure of variation, the coefficient of variation, shows that resource‐rich countries experience 60 per cent greater volatility in their growth than the global norm (Siegle, 2009, p. 47). Fatas and Mihov (2003, 2005) had shown that generally speaking, a country's average per capita growth rate over the period 1960–2000 is negatively correlated with output volatility of the government consumption share.…”
Section: Review Of Some Relevant Literaturementioning
confidence: 99%
“…Volatility in oil and mineral prices may thus have large impacts on the overall economy and on government budgets, causing greater uncertainty and lower growth (Havro and Santiso, 2008). A standard measure of variation, the coefficient of variation, shows that resource‐rich countries experience 60 per cent greater volatility in their growth than the global norm (Siegle, 2009, p. 47). Fatas and Mihov (2003, 2005) had shown that generally speaking, a country's average per capita growth rate over the period 1960–2000 is negatively correlated with output volatility of the government consumption share.…”
Section: Review Of Some Relevant Literaturementioning
confidence: 99%
“…The risk of violent conflict is significantly higher in mineral resource-rich countries than in countries with other abundant natural resources such as fertile land. Siegle (2007) found that hydrocarbon-rich countries were twice as likely as others to experience intrastate conflict, and Fearon (2005) showed that oil exports predicted higher civil war risk. The Bonn International Center for Conversion (http://www.bicc.de) has developed an index of resource governance and an index of conflict intensity, and has found a strong negative correlation between the quality of resource governance and the intensity of civil conflict.…”
Section: Extractive Resources and Conflictmentioning
confidence: 99%
“…The "resource curse" arguments refer not only to de-industrialization and slower growth rates but also to internal conflicts, autocratic regimes and corruption (Siegle, 2007). The existence of extensive natural resources is often associated with large FDI infiows as well as a poor governance environment.…”
Section: Resultsmentioning
confidence: 99%